Analysis of Student Traveled Distance and Pulse Rate in Technical Learning Model Implementation - Arief Abdul Malik; Lutfi Nur (TEGAR: Journal of Teaching Physical Education in Elementary School, 2022)
This study aimed to analyze the student traveled distance and pulse rate in the implementation of technical learning model in Physical Education subject. The descriptive method was used to obtain information and descriptions of the traveled distance and pulse rate of students during Physical Education learning. Participants involved in this study were 30 students (12-13 years), but only 8 students (4 boys and 4 girls) who used Polar GPS. The instruments used included Polar GPS RC3 to measure the traveled distance and Polar Heart Rate Sensor H3 to determine the students pulse rate. The results showed that the overall average of the student pulse rate was 137.13, which is categorized as the low to moderate category. Meanwhile, the average distance obtained was 0.48 km. It concludes that the student pulse rate during the implementation of the technical learning model in this study was in the low to moderate category. This study was limited to a small number of samples due to limited tools. Therefore, further research is needed to obtain a broader picture.